Eksklusi Sosial dalam Anggaran Publik Studi Kasus di Ngawi, Lamongan, dan Makasar - Toyibah, Dzuriyatun (Masyarakat: Jurnal Sosiologi, 2011)
The article aims to describe the process of social exclusion and inclusion within local government budget (APBD) in Lamongan and Ngawi East Java in 2006-2008, and Makasar South Sulawesi in 2009. Social exclusion was indicated by the absent of public participation in the decision making process. Social exclusion for public local budget appeared in regulation level such as unclear mechanism of public participation and the constraints to access budget documents. Those lead to avoid civil society to understand the real local budget. However, civil societies in three regions made several strategies to reduce social exclusion. The process was begun by the attempts to open public access for budget forums and budget documents by developing cooperation with member of local parliament. The next step of the process was inviting civil society organizations to attend budget deliberation forums to analyze the documents using a simple method to compare between public and apparatus expenditure. The result of budget analysis showed that public budget excluded public interest as the most important aspect of social exclusion in public budget.